Editor’s welcome - Angad S Chauhan; Lorna Pairman; William Ju; Joyce Guo (New Zealand Medical Student Journal)
Welcome to issue 37 of The New Zealand Medical Student Journal (NZMSJ), Te Hautaka o nga Akonga Rongoa. This issue focuses on the topic of work-life balance, an especially poignant concept given the constraints placed upon medical school training. The increasing complexity of medicine, together with resource constraints, and a progressively stretched workforce means doctors are experiencing immense stress. This was recognised in 2016 when a New Zealand-based cross-sectional study reported that 50% of sen- ior doctors experience high personal burnout.1 The rate for younger doctors is likely higher, with younger age being associated with in- creased personal burnout.1,2 As such, the relevance of ‘work-life bal- ance’ is being increasingly recognised in New Zealand. Internationally, the importance of ‘work-life balance’ has also been acknowledged, with the World Health Organisation including ‘burnout’ in the 11th Revision of the International Classification of Diseases in 2019. The issue of burnout is not isolated to doctors. Medical students have been noted to experience deterioration in mental health during their training, and at least half of medical students are affected by burnout during their medical careers.3-5 We acknowledge the increasing financial and workforce pressures placed on medical students, together with the continuing impacts of COVID-19 on medical placements. Whilst these pressures are not easily rectified, we hope this issue provides insight into ways students can manage and balance both university (work) and personal (life) commitments. We hope that you, as the reader, find value in the editorial articles published in this issue and find strategies to improve your own work-life balance during medical school and beyond.